(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: In the present study, the main objective was to develop a multiparticulate system containing chitosan microspheres for colon-specific drug delivery of capecitabine for the treatment of colorectal cancer. Materials and Methods: This study was based on the microbial degradability of chitosan microspheres. The microspheres were prepared with chitosan by emulsion cross linking method. A factorial design was applied to optimize the formulation. The effect of concentration of chitosan and drug: Polymer ratio was studied on particle size, % entrapment efficiency, and % drug release using 32 factorial designs. Results and Discussion: The prepared microspheres also analyzed for percentage yield, flow properties, and surface morphology. The results of analysis of variance test for responses measured indicated that the test is statistically significant. Conclusion: In vitro drug release studies were performed in a pH progression medium mimicking the conditions of the gastrointestinal tract showed a fast drug release initially demanded microencapsulation.